2013
DOI: 10.1002/jmri.24031
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient ratio between axillary lymph node with primary tumor to detect nodal metastasis in breast cancer patients

Abstract: ADC value and ADC ratio could be used as a reliable parameter to detect the axillary lymph nodes metastasis in breast cancer patients, and ADC ratio has a higher accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 17 publications
3
34
0
Order By: Relevance
“…The possible mechanism may be that the high cellularity or even necrosis in LNM producing by the cancerous mammary epithelial cells, may decreased the extracellular and intracellular spaces, and then restrict the mobility of water molecules and finally leading to the decreasing ADC values (Fornasa et al, 2012). These findings are in line with a previous study which also indicated that the ADC values of lymph nodes with metastasis were obviously lower compared to those of benign lymph nodes, which may provide a diagnostic value for the evaluation of LNM in BC (Luo et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The possible mechanism may be that the high cellularity or even necrosis in LNM producing by the cancerous mammary epithelial cells, may decreased the extracellular and intracellular spaces, and then restrict the mobility of water molecules and finally leading to the decreasing ADC values (Fornasa et al, 2012). These findings are in line with a previous study which also indicated that the ADC values of lymph nodes with metastasis were obviously lower compared to those of benign lymph nodes, which may provide a diagnostic value for the evaluation of LNM in BC (Luo et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, as for the step of screening, a flow chart of the study selection process was displayed in Figure 1. Initially, a total of 603 papers were selected from the 9 databases through screening the title and key words (Nakajo et al, 2010;Razek et al, 2010;Jeh et al, 2011;Nakai et al, 2011;Choi et al, 2012;Fornasa et al, 2012;Luo et al, 2012;Kamitani et al, 2013;Luo et al, 2013). Followed by excluding the duplicates (n=2), letters, reviews or meta-analysis (n=128), non-human studies (n=137), and the studies not related to research topics (n=145), the left studies (n=191) were reviewed and additional 179 studies were excluded in that they were not case-control or cohort study (n=48), not relevant to diffusion MRI (n=62), or not relevant to BC (n=69).…”
Section: Included Studiesmentioning
confidence: 99%
“…The data were analysed with SPSS ® software v. 19.0 (IBM Corporation, 2010, Armonk, NY). One-way ANOVA and a two-sided Student's t-test were used to evaluate data obtained from metastatic vs non-metastatic nodes.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although MRI has proven to be an invaluable tool for distinguishing RLN and cervical lymph node metastasis, 2,15,16 functional imaging, such as DWI, has been shown to facilitate diagnosis of lymph node metastasis in other malignant diseases. [17][18][19][20] Here, we evaluated the utility of DWI in differentiating metastatic from benign RLN in NPC, compared the accuracy of size-and ADC-based criteria in RLN metastasis and determined whether DWI would at all improve the diagnostic accuracy of RLN metastasis.…”
Section: Diagnosis Of Rln Metastasis With Dwimentioning
confidence: 99%
“…[17,18]. Diffusion-weighted MR imaging has also been used for characterization of mediastinal [19,20], abdominal [21], neck [22], and axillary [23] lymph nodes. Diffusion-weighted MR imaging has been used for evaluation of mediastinal [24], abdominal [25], and neck masses [26] in children.…”
Section: Introductionmentioning
confidence: 99%